César Vallejo or the smile beyond the tear - Gonzales, Carlos Enrique (Espergesia, 2018)
This work focuses on an almost reprehensive reflection of the discouragement that is presented in the studies on the playful exercise and the humor of César Vallejo in his work and reveals the profound importance of these elements, but without detracting from the humanitarian character. Take the playful and humorous aspects as a way to awaken the creation and develop sleeping skills, as an act of innate expression in the human being to, sometimes, rise to the dimension of a creator god that revitalizes the words endowing them with an infinite meaning, but this divine character never loses the characteristics of a suffering human being, as Vallejo expresses it in his poetic work; where it is sensitized to the extreme before everything that is living and natural; However, these situations are exploited to look for the ludic that reveals a deep philosophical concept